Simulated maturation process of the bitumens of the Pula oil shale, Hungary - Pápay László (Acta mineralogica-petrographica, 1985)
Maturation processes were carried out between 200 and 500 °C in the bitumens of the Pula oil shales, the alteration was traced partly by the thermal residue, partly by the IR and C—H analyses of the organic condensate. It was stated that the relatively high oxygen content of the Bit—A and BAM-bitumen is gradually lost by the release of compounds of different oxygen contents (carboxylic acids, ketons etc.) and by their decomposition, respectively. Above 400 °C no oxygen-bearing compound could be identified in the thermal residue. In case of both bitumens considerable part of the long paraffin chain and alicyclic skeleton is preserved up to 400 °C. At 450 °C the thermal residue contains very small quantities of paraffinic part in case of Bit—A, at the same temperature more paraffinic compounds survive the thermal effect in case of the BAM-bitumen. At 500 °C the difference between their thermal resistivity is manifested by the coke-like thermal residue of Bit—A and by the product of BAM-bitumen being similar to that of 450 °C. At lower temperatures the condensates are characterized by large quantities of oxygen-bearing compounds. The amount of these compounds is decreasing as a function of increasing temperature and mainly above 400 °C this value becomes ever lower, but the compounds can be detected even at 500 °C. The quantity of terminal defines increases parallel with the temperature. In the course of the simulated maturation processes the changes followed in the bitumen structure of the Pula oil shale show considerable similarities to those described in the thermal investigations of kerogens.